Performance analysis of the compact haematology analyser Sight OLO. (8th September 2022) - Leite, Rui; Woodcock, Sue; Brady, Sally; Bigsby, Charlotte; Webber, Kay; Daniel, Yvonne
Abstract: Introduction: Sight OLO is a compact full blood count (FBC) analyser that uses digital imaging techniques and artificial intelligence to count and assess cellular components of capillary or venous blood. It provides a FBC with a 5‐part white blood cell differential count. Our aim was to evaluate its performance against our standard analyser and optical microscopy. Methods: Comparative studies for the FBC parameters were done between the Sight OLO and the Unicel DxH800 analyser (Beckman Coulter). Evaluation comprised also repeatability studies and reproducibility studies. The flagging efficiency of the Sight OLO was assessed against the reference method (optical microscopy). Results: The SIGHT OLO showed a good comparability with the Unicel DxH800 analyser for most of the FBC parameters ( r > 0.9). The biases recorded between both equipments were within the manufacturer's target specifications for all the FBC parameters. The standard deviation and coefficient of variation calculated per parameter for the precision studies were within the manufacturer's target specifications for all FBC parameters, for all the variation components tested. The five alert flags assessed showed an overall efficiency above 75%, however, high frequency of false negatives was noted for some of the flags assessed. Conclusion: The evaluation of the Sight OLO showed that it can produce accurate FBC results, making it a suitable option for integration in several setups. Its innovative methodology gives it further potential to refine its capabilities.